Evidence for immunoglobulin Fc receptor-mediated prostaglandin2 and platelet-activating factor formation by cultured rat mesangial cells. - Neuwirth, R (1988)
The possibility of Fc-dependent uptake of IgG immune complexes was examined in subcultured rat mesangial cells free of monocytes. 195Au-labeled colloidal gold particles were coated either with BSA only or with BSA followed by rabbit anti-BSA-IgG or the F(ab')2 fragment of the IgG. Mesangial cells preferentially took up 195Au particles covered with BSA-anti-BSA-IgG over those covered with BSA or the F(ab')2 fragment. This uptake was a time-dependent and saturable process inhibitable by sodium azide or cytochalasin B. Using phase-contrast microscopy in the light reflectance mode, it was established that essentially all mesangial cells took up IgG-coated gold particles. By electron microscopy the process was shown to consist of vesicular uptake with delivery to endosomes. Mesangial binding-uptake of the IgG-covered particles was associated with stimulation of PGE2 synthesis and production of platelet-activating factor, a lipid mediator of inflammation. To characterize the potential Fc receptor for IgG we used the rosetting technique with sheep red blood cells coated with IgG subclass-specific mouse monoclonal antibodies. 50% of mesangial cells exhibited rosetting with red cells coated with mouse IgG2a, whereas negligible rosetting was observed with IgG2b or IgG1. Competition experiments confirmed the specificity of IgG2a binding. We conclude that cultured rat mesangial cells exhibit specific receptors for IgG and that occupancy of Fc receptors results in endocytosis and is associated with generation of PGE2 and platelet-activating factor. These observations may be of significance for immune-mediated glomerular diseases.